Opthalmoplegic Migrane with Recurrent Sixth Nerve Palsy: A Rare Presentation of Headache in a Young Lady - Chowdhury, Monzurul H; Nur, Zannatun; Begum, Hosne Ara; Mahbub, Md Shahriar; Ahasan, HAM Nazmul (Journal of Medicine, 2009)
Migraine is a common presentation of headache but migraine with opthalmoplegia with third nerve palsy is rare and with fourth or sixth nerve palsy is very rare. Although it represents a benign course, duration and severity are variable among the patients. We demonstrated a young lady presenting with right hemicranial headache for 12 days with several episodes of vomiting. She also complained of double vision for 7 days. The headache started from the inner canthus of right eye and gradually spread throughout the right half of head over 2 hours and was throbbing in nature. She also complained of double vision from 5th day after onset of headache. Interestingly, she informed similar types of attack for two episodes in last 1 year which persisted for around 22-25 days each time. On examination, she appeared ill looking with convergent squint on right lateral gaze. Cranial nerves examinations showed all the cranial nerves were intact except right sixth cranial nerve palsy. Laboratory investigations and neuroimaging were normal. Our case fulfilled the International Classification of Headache Disorders (ICHD II) criteria for opthalmoplegic migraine with recurrent six nerve palsy which responded dramatically with prednisolone therapy 1mg/kg/day which also prevented recurrence within 6 months. Keyword: Migraine, Opthalmoplegic migraine, Abducens nerve palsy. doi: 10.3329/jom.v10i2.2833 J MEDICINE 2009; 10 : 139-141